ANALISIS PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMAHAMAN PEMBELAJARAN FISIKA DI SMAN 1 AMPEK ANGKEK - Rina Andriyeni; Supratman Zakir (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. The rapid development of technology in education supports the use of advanced technology in learning, one of which is artificial intelligence. Artificial Intelligence is an artificial intelligence technology designed to work according to human wants and needs in a short time, one of which is Gamma.App and Google Assistant. The involvement of Artificial Intelligence certainly increases the transfer of knowledge for students in understanding Physics lessons in the classroom. Physics learning requires an understanding of basic theoretical knowledge which is later used to solve physics problems in mathematical equations. Physics learning in this case is limited to Straight Motion material. This research is designed as a literature study and observation research. The results of the analysis showed that the use of Artificial Intelligence found that: students' ability to understand physics with the use of Artificial Intelligence is included in the high category, students' ability to understand physics without the use of Artificial Intelligence is included in the medium category, students' ability to solve physics problems mathematically in accordance with the theory with the use of Artificial Intelligence is included in the high category and students' ability to solve physics problems mathematically in accordance with the theory without the use of Artificial Intelligence is included in the medium category.